Sosialisasi Dan Penyuluhan Hukum Tentang Aborsi Menurut Hukum Pidana Dan Undang-Undang Kesehatan Di SMK Farmasi Bintang Harapan Cibarusah, Kabupaten Bekasi - Tarina, Arum; Prawitasari, Nining Yurista (Jurnal Pengabdian kepada Masyarakat UBJ, 2023)
This Community Service activity aims to provide socialization and counseling to the students of the Bintang Harapan Nursing Pharmacy Vocational School so they can learn about the legal aspects of abortion. With this socialization and counseling, it is hoped that the students of the Bintang Harapan Nursing Pharmacy Vocational School can be careful and scrupulous about matters relating to legal aspects of abortion and the applicable professional ethics. This community service activity method uses interaction quiz methods, counseling, discussions, and case study learning practiced by participants and lecturers. The implementation of this community service involved lecturers at the Pelita Bangsa University Law Study Program in collaboration with the Bintang Harapan Pharmacy Vocational School, Cibarusah District, Bekasi Regency, West Java as the target subject.